Clinical determinants and prognostic implications of renin and aldosterone in patients with symptomatic heart failure - Masatake Kobayashi; Susan Stienen; Jozine M. terMaaten; Kenneth Dickstein; Nilesh J. Samani; Chim C. Lang; Leong L. Ng; Stefan D. Anker; Macro Metra; Gregoire Preud'homme; Kevin Duarte; Zohra Lamiral; et al. (ESC Heart Failure)
Abstract Aims Activation of the renin–angiotensin–aldosterone system plays an important role in the pathophysiology of heart failure (HF) and has been associated with poor prognosis. There are limited data on the associations of renin and aldosterone levels with clinical profiles, treatment response, and study outcomes in patients with HF. Methods and results We analysed 2,039 patients with available baseline renin and aldosterone levels in BIOSTAT‐CHF (a systems BIOlogy study to Tailored Treatment in Chronic Heart Failure). The primary outcome was the composite of all‐cause mortality or HF hospitalization. We also investigated changes in renin and aldosterone levels after administration of mineralocorticoid receptor antagonists (MRAs) in a subset of the EPHESUS trial and in an acute HF cohort (PORTO). In BIOSTAT‐CHF study, median renin and aldosterone levels were 85.3 (percentile25–75 = 28–247) μIU/mL and 9.4 (percentile25–75 = 4.4–19.8) ng/dL, respectively. Prior HF admission, lower blood pressure, sodium, poorer renal function, and MRA treatment were associated with higher renin and aldosterone. Higher renin was associated with an increased rate of the primary outcome [highest vs. lowest renin tertile: adjusted‐HR (95% CI) = 1.47 (1.16–1.86), P = 0.002], whereas higher aldosterone was not [highest vs. lowest aldosterone tertile: adjusted‐HR (95% CI) = 1.16 (0.93–1.44), P = 0.19]. Renin and/or aldosterone did not improve the BIOSTAT‐CHF prognostic models. The rise in aldosterone with the use of MRAs was observed in EPHESUS and PORTO studies. Conclusions Circulating levels of renin and aldosterone were associated with both the disease severity and use of MRAs. By reflecting both the disease and its treatments, the prognostic discrimination of these biomarkers was poor. Our data suggest that the “point” measurement of renin and aldosterone in HF is of limited clinical utility.